DEMAND AND MARKET CONCENTRATION FOR BRANDED SAUSAGE ROLLS IN OYO STATE, NIGERIA - Adejoke Modinat Adedeji; Fatai Abiola Sowunmi (Agricultural Socio-Economics Journal, 2022)
Branded sausage is one of the fast foods, and the demand for it in Nigeria is increasing substantially due to growing household affluence and its availability and affordability. The study examined the market concentration and the need for branded sausage rolls in Oyo State using 290 respondents (buyers and sellers) collected through a three-stage sampling procedure. The study affirmed that Gala (small and big) had the highest percentage (41.3%) of consumers while bigi and the rite spicy had 22.7% and 21.4%, respectively. The yum-yum brand had the lowest consumers percentage (1.8%). The average amount consumers spent on gala (big and small size) per month was ₦824.18 followed by rite spicy and bigi with a moderate amount of ₦582.98 and ₦520 per month. Gala (small and big) had the highest inequality in sales revenue (0.42) while bigi had the least (0.26). The market concentration of gala was the highest (50%) while bigi had the least (40%). The market share of the gala (big and small size) was 54.4 percent followed by rite spicy and bigi with 23.9 and 21.1 percent, respectively. Monthly income, taste, quality, price, and availability influenced consumers' preference for sausage rolls while monthly payment, household size and brand consumed determined consumers' monthly expenditure on sausage rolls in the study area. The yum-yum brand had the lowest consumer’s percentages in the sausage market at 1.8%. Producers of other sausage rolls brands should develop strategies that would ensure fair competition with other brands so that the dominance of some brands can be reduced to prevent the emergence of a monopolist in the sausage rolls market. The need for market segmentation based on consumers’ income is recommended.